2020
DOI: 10.3390/ijms21082790
|View full text |Cite
|
Sign up to set email alerts
|

Sweroside Prevents Non-Alcoholic Steatohepatitis by Suppressing Activation of the NLRP3 Inflammasome

Abstract: Non-alcoholic steatohepatitis (NASH), a type of non-alcoholic fatty liver disease, is characterized as steatosis and inflammation in the liver. NLRP3 inflammasome activation is associated with NASH pathology. We hypothesized that suppressing the NLRP3 inflammasome could be effective in preventing NASH. We searched substances that could inhibit the activation of the NLRP3 inflammasome and identified sweroside as an NLRP3 inhibitor. We investigated whether sweroside can be applied to prevent the pathological sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…In the present study, we found that sweroside inhibited the expression levels of NLRP3, ASC, IL-1β, and cleaved caspase-1, which suggested that sweroside could repress NLRP3 inflammasome-mediated pyroptosis. This was consistent with findings by Yang et al ( 21 ). In the process of IR, ROS largely accumulate in the tissue and induce NLRP3 inflammasome activation ( 34 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, we found that sweroside inhibited the expression levels of NLRP3, ASC, IL-1β, and cleaved caspase-1, which suggested that sweroside could repress NLRP3 inflammasome-mediated pyroptosis. This was consistent with findings by Yang et al ( 21 ). In the process of IR, ROS largely accumulate in the tissue and induce NLRP3 inflammasome activation ( 34 ).…”
Section: Discussionsupporting
confidence: 94%
“…Yang et al revealed that sweroside alleviated non-alcoholic fatty liver disease in obese mice via the modulation of lipid metabolism and inflammation ( 29 ). In addition, Yang et al indicated that sweroside protected against non-alcoholic steatohepatitis by inhibiting NLRP3 inflammasome-mediated pyroptosis ( 21 ). More interestingly, sweroside has been found to prevent myocardial cells against aconitine-induced cardiac toxicity ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can effectively inhibit NLRP3 inflammasome activation in bone marrow-derived macrophages (BMDMs). Additionally, in a mouse model of nonalcoholic steatohepatitis (NASH) induced by a methionine-choline-deficient (MCD) diet, sweroside significantly attenuates NASH symptoms (including liver fibrosis) through the suppression of NLRP3 inflammasome activation in the liver, partially by inhibiting de novo synthesis of mitochondrial DNA (mtDNA), which can be oxidized to serve as the ultimate NLRP3 ligand, or at least a part of it, thus activating NLRP3 inflammasome complexes after exposure to LPS and NLRP3 activators (Zhong et al, 2018;Yang et al, 2020).…”
Section: Monoterpenoidsmentioning
confidence: 99%
“…Therefore, the discovery of inhibitors of NLRP3 inflammasome activation from bioactive compounds derived from natural substances might be a promising future strategy for the prevention and treatment of neurodegenerative diseases. Our study showed that β-carotene, sweroside, and sulforaphane [ 57 , 58 , 59 ], acting as NLRP3 inhibitors, might be applicable to the prevention of AD and PD.…”
Section: Discussionmentioning
confidence: 99%